Recent advances in the gold-catalyzed additions to C–C multiple bonds - Huang, He; Zhou, Yu; Liu, Hong (Beilstein Journal of Organic Chemistry, 2011)
C–O, C–N and C–C bonds are the most widespread types of bonds in nature, and are the cornerstone of most organic compounds, ranging from pharmaceuticals and agrochemicals to advanced materials and polymers. Cationic gold acts as a soft and carbophilic Lewis acid and is considered one of the most powerful activators of C–C multiple bonds. Consequently, gold-catalysis plays an important role in the development of new strategies to form these bonds in more convenient ways. In this review, we highlight recent advances in the gold-catalyzed chemistry of addition of X–H (X = O, N, C) bonds to C–C multiple bonds, tandem reactions, and asymmetric additions. This review covers gold-catalyzed organic reactions published from 2008 to the present.
Keywords: asymmetric addition; catalysis; gold; C−C multiple bonds; tandem reaction

(untitled) - Hashmi, A. S. K.; Bührle, M. (Aldrichimica Acta, 2010)

(untitled) - Shapiro, N. D.; Toste, F. D. (Synlett, 2010)

(untitled) - Patil, N. T.; Yamamoto, Y. (ARKIVOC, 2007)

(untitled) - Hashmi, A. S. K. (Pure Appl. Chem., 2010)

(untitled) - Bandini, M. (Chem. Soc. Rev., 2011)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Shen, H. C. (Tetrahedron, 2008)

(untitled) - Shen, H. C. (Tetrahedron, 2008)

(untitled) - Fürstner, A.; Davies, P. W. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hashmi, A. S. K.; Hutchings, G. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Muzart, J. (Tetrahedron, 2008)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Skouta, R.; Li, C.-J. (Tetrahedron, 2008)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Commun., 2007)

(untitled) - Corma, A.; Leyva-Pérez, A.; Sabater, M. J. (Chem. Rev., 2011)

(untitled) - Eom, D.; Kang, D.; Lee, P. H. (J. Org. Chem., 2010)

(untitled) - Balamurugan, R.; Koppolu, S. R. (Tetrahedron, 2009)

(untitled) - Du, X. W.; Song, F. J.; Lu, Y. H.; Chen, H. Y.; Liu, Y. H. (Tetrahedron, 2009)

(untitled) - Kim, S.; Kang, D.; Shin, S.; Lee, P. H. (Tetrahedron Lett., 2010)

(untitled) - Aponick, A.; Li, C.-Y.; Malinge, J.; Marques, E. F. (Org. Lett., 2009)

(untitled) - Aponick, A.; Biannic, B. (Synthesis, 2008)

(untitled) - Bandini, M.; Monari, M.; Romaniello, A.; Tragni, M. (Chem.–Eur. J., 2010)

(untitled) - Aksin, Ö.; Krause, N. (Adv. Synth. Catal., 2008)

(untitled) - Rüttinger, R.; Leutzow, J.; Wilsdorf, M.; Wilckens, K.; Czekelius, C. (Org. Lett., 2011)

(untitled) - Wilckens, K.; Uhlemann, M.; Czekelius, C. (Chem.–Eur. J., 2009)

(untitled) - Liu, L.-P.; Hammond, G. B. (Org. Lett., 2009)

(untitled) - Aponick, A.; Li, C.-Y.; Palmes, J. A. (Org. Lett., 2009)

(untitled) - Zhang, Y.; Xue, J. J.; Xin, Z. J.; Xie, Z. X.; Li, Y. (Synlett, 2008)

(untitled) - Bauer, J. T.; Hadfield, M. S.; Lee, A.-L. (Chem. Commun., 2008)

(untitled) - Hadfield, M. S.; Bauer, J. T.; Glen, P. E.; Lee, A. L. (Org. Biomol. Chem., 2010)

(untitled) - Corma, A.; Ruiz, V. R.; Leyva-Pérez, A.; Sabater, M. J. (Adv. Synth. Catal., 2010)

(untitled) - Schuler, M.; Silva, F.; Bobbio, C.; Tessier, A.; Gouverneur, V. (Angew. Chem., Int. Ed., 2008)

(untitled) - Hirai, T.; Hamasaki, A.; Nakamura, A.; Tokunaga, M. (Org. Lett., 2009)

(untitled) - Cuenca, A. B.; Mancha, G.; Asensio, G.; Medio-Simon, M. (Chem.–Eur. J., 2008)

(untitled) - Ye, L. W.; Cui, L.; Zhang, G. Z.; Zhang, L. M. (J. Am. Chem. Soc., 2010)

(untitled) - Cordonnier, M.-C.; Blanc, A.; Pale, P. (Org. Lett., 2008)

(untitled) - Li, Y.; Tang, P. P.; Chen, Y. X.; Yu, B. (J. Org. Chem., 2008)

(untitled) - Götze, S.; Fitzner, R.; Kunz, H. (Synlett, 2009)

(untitled) - Sureshkumar, G.; Hotha, S. (Chem. Commun., 2008)

(untitled) - Li, Y.; Yang, X. Y.; Liu, Y. P.; Zhu, C. S.; Yang, Y.; Yu, B. (Chem.–Eur. J., 2010)

(untitled) - Thadke, S. A.; Hotha, S. (Tetrahedron Lett., 2010)

(untitled) - Belting, V.; Krause, N. (Org. Biomol. Chem., 2009)

(untitled) - Belot, S.; Vogt, K. A.; Besnard, C.; Krause, N.; Alexakis, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Liu, L. P.; Hammond, G. B. (Org. Lett., 2010)

(untitled) - Kotera, A.; Uenishi, J.; Uemura, M. (J. Organomet. Chem., 2010)

(untitled) - Seraya, E.; Slack, E.; Ariafard, A.; Yates, B. F.; Hyland, C. J. T. (Org. Lett., 2010)

(untitled) - Wang, Y. H.; Zhu, L. L.; Zhang, Y. X.; Chen, Z. L. (Chem. Commun., 2010)

(untitled) - Liu, L.-P.; Xu, B.; Mashuta, M. S.; Hammond, G. B. (J. Am. Chem. Soc., 2008)

(untitled) - Shi, Y. L.; Roth, K. E.; Ramgren, S. D.; Blum, S. A. (J. Am. Chem. Soc., 2009)

(untitled) - Pennell, M. N.; Unthank, M. G.; Turner, P.; Sheppard, T. D. (J. Org. Chem., 2011)

(untitled) - Buzas, A. K.; Istrate, F. M.; Gagosz, F. (Tetrahedron, 2009)

(untitled) - Ye, L.; He, W.; Zhang, L. (J. Am. Chem. Soc., 2010)

(untitled) - Widenhoefer, R. A.; Han, X. Q. (Eur. J. Org. Chem., 2006)

(untitled) - Sun, H.; Su, F.-Z.; Ni, J.; Cao, Y.; He, H.-Y.; Fan, K. N. (Angew. Chem., Int. Ed., 2009)

(untitled) - He, L.; Lou, X. B.; Ni, J.; Liu, Y. M.; Cao, Y.; He, H. Y.; Fan, K. N. (Chem.–Eur. J., 2010)

(untitled) - Zeng, X. M.; Soleilhavoup, M.; Bertrand, G. (Org. Lett., 2009)

(untitled) - Hill, A. W.; Elsegood, M. R. J.; Kimber, M. C. (J. Org. Chem., 2010)

(untitled) - Hesp, K. D.; Stradiotto, M. (J. Am. Chem. Soc., 2010)

(untitled) - Mukherjee, P.; Widenhoefer, R. A. (Org. Lett., 2011)

(untitled) - Nakamura, I.; Okamoto, M.; Terada, M. (Org. Lett., 2010)

(untitled) - Benedetti, E.; Lemière, G.; Chapellet, L.-L.; Penoni, A.; Palmisano, G.; Malacria, M.; Goddard, J.-P.; Fensterbank, L. (Org. Lett., 2010)

(untitled) - Ye, D. J.; Wang, J. F.; Zhang, X.; Zhou, Y.; Ding, X.; Feng, E. G.; Sun, H. F.; Liu, G. N.; Jiang, H. L.; Liu, H. (Green Chem., 2009)

(untitled) - Li, H.; Widenhoefer, R. A. (Org. Lett., 2009)

(untitled) - Iglesias, A.; Muñiz, K. (Chem.–Eur. J., 2009)

(untitled) - Mukherjee, P.; Widenhoefer, R. A. (Org. Lett., 2010)

(untitled) - Nakamura, I.; Yamagishi, U.; Song, D.; Konta, S.; Yamamoto, Y. (Chem.–Asian J., 2008)

(untitled) - Surmont, R.; Verniest, G.; De Kimpe, N. (Org. Lett., 2009)

(untitled) - Gouault, N.; Le Roch, M.; Cornée, C.; David, M.; Uriac, P. (J. Org. Chem., 2009)

(untitled) - Huang, J. F.; Huang, X.; Liu, B. (Org. Biomol. Chem., 2010)

(untitled) - Bates, R. W.; Dewey, M. R. (Org. Lett., 2009)

(untitled) - Ye, S. Y.; Yu, Z.-X. (Org. Lett., 2010)

(untitled) - Shu, X.-Z.; Liu, X.-Y.; Xiao, H.-Q.; Ji, K.-G.; Guo, L.-N.; Liang, Y.-M. (Adv. Synth. Catal., 2008)

(untitled) - Saito, A.; Konishi, T.; Hanzawa, Y. (Org. Lett., 2010)

(untitled) - Shapiro, N. D.; Shi, Y.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Chen, D.-D.; Hou, X.-L.; Dai, L.-X. (Tetrahedron Lett., 2009)

(untitled) - Davies, P. W.; Martin, N. (Org. Lett., 2009)

(untitled) - Davies, P. W.; Martin, N. (J. Organomet. Chem., 2011)

(untitled) - Du, X. W.; Xie, X.; Liu, Y. H. (J. Org. Chem., 2010)

(untitled) - Kothandaraman, P.; Foo, S. J.; Chan, P. W. H. (J. Org. Chem., 2009)

(untitled) - Zhang, L.; Ye, D. J.; Zhou, Y.; Liu, G. N.; Feng, E. G.; Jiang, H. L.; Liu, H. (J. Org. Chem., 2010)

(untitled) - Ye, D.; Zhang, X.; Zhou, Y.; Zhang, D.; Zhang, L.; Wang, H.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2009)

(untitled) - Ibrahim, N.; Hashmi, A. S. K.; Rominger, F. (Adv. Synth. Catal., 2011)

(untitled) - Huo, Z. B.; Yamamoto, Y. (Tetrahedron Lett., 2009)

(untitled) - Zhang, G. Z.; Peng, Y.; Cui, L.; Zhang, L. M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Kimber, M. C. (Org. Lett., 2010)

(untitled) - Li, P. H.; Wang, L.; Wang, M.; You, F. (Eur. J. Org. Chem., 2008)

(untitled) - Xie, C. S.; Zhang, Y. H.; Yang, Y. Z. (Chem. Commun., 2008)

(untitled) - Tarselli, M. A.; Liu, A.; Gagne, M. R. (Tetrahedron, 2009)

(untitled) - Brand, J. P.; Charpentier, J.; Waser, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Kar, A.; Mangu, N.; Kaiser, H. M.; Beller, M.; Tse, M. K. (Chem. Commun., 2008)

(untitled) - Barluenga, J.; Tudela, E.; Vicente, R.; Ballesteros, A.; Tomás, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, C. K.; Zeng, Y.; Zhang, H.; Feng, J. J.; Zhang, Y.; Wang, J. B. (Angew. Chem., Int. Ed., 2010)

(untitled) - Li, C.-W.; Pati, K.; Lin, G.-Y.; Abu Sohel, S. M.; Hung, H.-H.; Liu, R.-S. (Angew. Chem., Int. Ed., 2010)

(untitled) - Zou, Y.; Garayalde, D.; Wang, Q. R.; Nevado, C.; Goeke, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Horino, Y.; Yamamoto, T.; Ueda, K.; Kuroda, S.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Patil, N. T.; Yamamoto, Y. (Chem. Rev., 2008)

(untitled) - Chaudhuri, R.; Liao, H.-Y.; Liu, R.-S. (Chem.–Eur. J., 2009)

(untitled) - Benitez, D.; Tkatchouk, E.; Gonzalez, A. Z.; Goddard, W. A., III; Toste, F. D. (Org. Lett., 2009)

(untitled) - Mauleón, P.; Zeldin, R. M.; González, A. Z.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Alonso, I.; Trillo, B.; López, F.; Montserrat, S.; Ujaque, G.; Castedo, L.; Lledós, A.; Mascareñas, J. L. (J. Am. Chem. Soc., 2009)

(untitled) - Cui, L.; Peng, Y.; Zhang, L. M. (J. Am. Chem. Soc., 2009)

(untitled) - Teng, T.-M.; Liu, R.-S. (J. Am. Chem. Soc., 2010)

(untitled) - Kusama, H.; Karibe, Y.; Onizawa, Y.; Iwasawa, N. (Angew. Chem., Int. Ed., 2010)

(untitled) - Gao, H. Y.; Wu, X. X.; Zhang, J. L. (Chem. Commun., 2010)

(untitled) - Hsu, Y.-C.; Datta, S.; Ting, C.-M.; Liu, R.-S. (Org. Lett., 2008)

(untitled) - Shapiro, N. D.; Toste, F. D. (J. Am. Chem. Soc., 2008)

(untitled) - Gung, B. W.; Craft, D. T.; Bailey, L. N.; Kirschbaum, K. (Chem.–Eur. J., 2010)

(untitled) - Leseurre, L.; Chao, C.-M.; Seki, T.; Genin, E.; Toullec, P. Y.; Genêt, J.-P.; Michelet, V. (Tetrahedron, 2009)

(untitled) - Lee, J. C. H.; Hall, D. G. (Tetrahedron Lett., 2011)

(untitled) - Li, G. J.; Liu, Y. H. (J. Org. Chem., 2010)

(untitled) - Chen, Z. L.; Zhang, Y.-X.; Wang, Y.-H.; Zhu, L.-L.; Liu, H.; Li, X.-X.; Guo, L. (Org. Lett., 2010)

(untitled) - Toullec, P. Y.; Blarre, T.; Michelet, V. (Org. Lett., 2009)

(untitled) - Escribano-Cuesta, A.; López-Carrillo, V.; Janssen, D.; Echavarren, A. M. (Chem.–Eur. J., 2009)

(untitled) - Echavarren, A. M.; Jiménez-Núñez, E. (Top. Catal., 2010)

(untitled) - Sperger, C.; Fiksdahl, A. (Org. Lett., 2009)

(untitled) - Sperger, C. A.; Fiksdahl, A. (J. Org. Chem., 2010)

(untitled) - Meng, J.; Zhao, Y.-L.; Ren, C.-Q.; Li, Y.; Li, Z.; Liu, Q. (Chem.–Eur. J., 2009)

(untitled) - Sperger, C.; Strand, L. H. S.; Fiksdahl, A. (Tetrahedron, 2010)

(untitled) - Cheong, P. H.-Y.; Morganelli, P.; Luzung, M. R.; Houk, K. N.; Toste, F. D. (J. Am. Chem. Soc., 2008)

(untitled) - Imase, H.; Noguchi, K.; Hirano, M.; Tanaka, K. (Org. Lett., 2008)

(untitled) - Lee, Y. T.; Kang, Y. K.; Chung, Y. K. (J. Org. Chem., 2009)

(untitled) - Barabé, F.; Bétournay, G.; Bellavance, G.; Barriault, L. (Org. Lett., 2009)

(untitled) - Michon, C.; Liu, S. Y.; Hiragushi, S.; Uenishi, J.; Uemura, M. (Tetrahedron, 2008)

(untitled) - Jiménez-Núñez, E.; Molawi, K.; Echavarren, A. M. (Chem. Commun., 2009)

(untitled) - Amijs, C. H. M.; López-Carrillo, V.; Raducan, M.; Pérez-Galán, P.; Ferrer, C.; Echavarren, A. M. (J. Org. Chem., 2008)

(untitled) - Schelwies, M.; Moser, R.; Dempwolff, A. L.; Rominger, F.; Helmchen, G. (Chem.–Eur. J., 2009)

(untitled) - Porcel, S.; López-Carrillo, V.; García-Yebra, C.; Echavarren, A. M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Zhu, L.-L.; Wang, Y.-H.; Zhang, Y.-X.; Li, X.-X.; Liu, H.; Chen, Z. (J. Org. Chem., 2011)

(untitled) - Miege, F.; Meyer, C.; Cossy, J. (Org. Lett., 2010)

(untitled) - Sanz, R.; Miguel, D.; Rodríguez, F. (Angew. Chem., Int. Ed., 2008)

(untitled) - Barluenga, J.; Piedrafita, M.; Ballesteros, A.; Suárez-Sobrino, A. L.; González, J. M. (Chem.–Eur. J., 2010)

(untitled) - Ferrer, C.; Escribano-Cuesta, A.; Echavarren, A. M. (Tetrahedron, 2009)

(untitled) - Gronnier, C.; Odabachian, Y.; Gagosz, F. (Chem. Commun., 2011)

(untitled) - Park, C.; Lee, P. H. (Org. Lett., 2008)

(untitled) - Balamurugan, R.; Gudla, V. (Org. Lett., 2009)

(untitled) - Tarselli, M. A.; Gagné, M. R. (J. Org. Chem., 2008)

(untitled) - Kong, W.; Fu, C.; Ma, S. (Eur. J. Org. Chem., 2010)

(untitled) - Jurberg, I. D.; Gagosz, F. (J. Organomet. Chem., 2011)

(untitled) - Hashmi, A. S. K.; Rudolph, M.; Huck, J.; Frey, W.; Bats, J. W.; Hamzić, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Bhunia, S.; Liu, R.-S. (J. Am. Chem. Soc., 2008)

(untitled) - Zhou, J. (Chem.–Asian J., 2010)

(untitled) - Chen, Y.; Li, G.; Liu, Y. (Adv. Synth. Catal., 2011)

(untitled) - Chen, Y.; Lu, Y.; Li, G.; Liu, Y. (Org. Lett., 2009)

(untitled) - Lu, Y.; Du, X.; Jia, X.; Liu, Y. (Adv. Synth. Catal., 2009)

(untitled) - Zhang, Q.; Cheng, M.; Hu, X.; Li, B.-G.; Ji, J.-X. (J. Am. Chem. Soc., 2010)

(untitled) - Barluenga, J.; Fernández-Rodríguez, M. A.; García-García, P.; Aguilar, E. (J. Am. Chem. Soc., 2008)

(untitled) - Li, C.-J.; Trost, B. M. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Hirano, K.; Inaba, Y.; Takahashi, N.; Shimano, M.; Oishi, S.; Fujii, N.; Ohno, H. (J. Org. Chem., 2011)

(untitled) - Dudnik, A. S.; Schwier, T.; Gevorgyan, V. (Org. Lett., 2008)

(untitled) - Jin, T.; Yamamoto, Y. (Org. Lett., 2008)

(untitled) - Liu, Y.; Qian, J.; Lou, S.; Xu, Z. (J. Org. Chem., 2010)

(untitled) - Ueda, M.; Sato, A.; Ikeda, Y.; Miyoshi, T.; Naito, T.; Miyata, O. (Org. Lett., 2010)

(untitled) - Liu, L.; Zhang, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hirano, K.; Inaba, Y.; Watanabe, T.; Oishi, S.; Fujii, N.; Ohno, H. (Adv. Synth. Catal., 2010)

(untitled) - Kothandaraman, P.; Rao, W.; Foo, S. J.; Chan, P. W. H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hopkinson, M. N.; Tessier, A.; Salisbury, A.; Giuffredi, G. T.; Combettes, L. E.; Gee, A. D.; Gouverneur, V. (Chem.–Eur. J., 2010)

(untitled) - García-García, P.; Fernández-Rodríguez, M. A.; Aguilar, E. (Angew. Chem., Int. Ed., 2009)

(untitled) - Liu, Y.; Xu, W.; Wang, X. (Org. Lett., 2010)

(untitled) - Zhou, Y.; Zhai, Y.; Ji, X.; Liu, G.; Feng, E.; Ye, D.; Zhao, L.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2010)

(untitled) - Feng, E.; Zhou, Y.; Zhang, D.; Zhang, L.; Sun, H.; Jiang, H.; Liu, H. (J. Org. Chem., 2010)

(untitled) - Zhou, Y.; Li, J.; Ji, X.; Zhou, W.; Zhang, X.; Qian, W.; Jiang, H.; Liu, H. (J. Org. Chem., 2011)

(untitled) - Zhou, Y.; Ji, X.; Liu, G.; Zhang, D.; Zhao, L.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2010)

(untitled) - Patil, N. T.; Mutyala, A. K.; Lakshmi, P. G. V. V.; Gajula, B.; Sridhar, B.; Pottireddygari, G. R.; Rao, T. P. (J. Org. Chem., 2010)

(untitled) - Zhou, Y.; Feng, E.; Liu, G.; Ye, D.; Li, J.; Jiang, H.; Liu, H. (J. Org. Chem., 2009)

(untitled) - Zhang, G.; Cui, L.; Wang, Y.; Zhang, L. (J. Am. Chem. Soc., 2010)

(untitled) - Brenzovich, W. E.; Benitez, D.; Lackner, A. D.; Shunatona, H. P.; Tkatchouk, E.; Goddard, W. A., III; Toste, F. D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Ball, L. T.; Green, M.; Lloyd-Jones, G. C.; Russell, C. A. (Org. Lett., 2010)

(untitled) - Melhado, A. D.; Brenzovich, W. E.; Lackner, A. D., Jr; Toste, F. D. (J. Am. Chem. Soc., 2010)

(untitled) - Jadhav, A. M.; Bhunia, S.; Liao, H.-Y.; Liu, R.-S. (J. Am. Chem. Soc., 2011)

(untitled) - Hopkinson, M. N.; Ross, J. E.; Giuffredi, G. T.; Gee, A. D.; Gouverneur, V. (Org. Lett., 2010)

(untitled) - Suárez-Pantiga, S.; Rubio, E.; Alvarez-Rúa, C.; González, J. M. (Org. Lett., 2009)

(untitled) - Barluenga, J.; Fernández, A.; Rodríguez, F.; Fañanás, F. J. (Chem.–Eur. J., 2009)

(untitled) - Ding, C.-H.; Hou, X.-L. (Chem. Rev., 2011)

(untitled) - Monge, D.; Jensen, K. L.; Franke, P. T.; Lykke, L.; Jørgensen, K. A. (Chem.–Eur. J., 2010)

(untitled) - Matsumoto, Y.; Selim, K. B.; Nakanishi, H.; Yamada, K.; Yamamoto, Y.; Tomioka, K. (Tetrahedron Lett., 2010)

(untitled) - LaLonde, R. L.; Wang, Z. J.; Mba, M.; Lackner, A. D.; Toste, F. D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Murai, M.; Uenishi, J.; Uemura, M. (Org. Lett., 2010)

(untitled) - Wang, C.; Han, Z.-Y.; Luo, H.-W.; Gong, L.-Z. (Org. Lett., 2010)

(untitled) - Chao, C.-M.; Vitale, M. R.; Toullec, P. Y.; Genêt, J.-P.; Michelet, V. (Chem.–Eur. J., 2009)

(untitled) - Bandini, M.; Eichholzer, A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Bandini, M.; Gualandi, A.; Monari, M.; Romaniello, A.; Savoia, D.; Tragni, M. (J. Organomet. Chem., 2011)

(untitled) - Chao, C. M.; Beltrami, D.; Toullec, P. Y.; Michelet, V. (Chem. Commun., 2009)

(untitled) - Zhou, G.; Liu, F.; Zhang, J. (Chem.–Eur. J., 2011)

(untitled) - Sethofer, S. G.; Mayer, T.; Toste, F. D. (J. Am. Chem. Soc., 2010)

(untitled) - Uemura, M.; Watson, I. D. G.; Katsukawa, M.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Kleinbeck, F.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Liu, F.; Yu, Y.; Zhang, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Martínez, A.; García-García, P.; Fernández-Rodríguez, M. A.; Rodríguez, F.; Sanz, R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Muratore, M. E.; Holloway, C. A.; Pilling, A. W.; Storer, R. I.; Trevitt, G.; Dixon, D. J. (J. Am. Chem. Soc., 2009)